Answer:
x = 2
y = -3
Step-by-step explanation:
Solve by substitution:
2x - y = 7
Move the 2x to the other side: -y = 7 - 2x
Divide by -1: y = -7 + 2x
Take the other equation: 3x + y = 3
Substitute y in: 3x + (-7 + 2x) = 3
Take out the parenthesis: 3x - 7 + 2x = 3
Move -7 to the other side: 3x + 2x = 3 + 7
Simplify: 5x = 10
x = 2
Take the first equation: 2x - y = 7
Substitute x back in: 2(2) - y = 7
Simplify: 4 - y = 7
-y = 3
y = -3
Answer:
125*125
Step-by-step explanation:
5^6 means 6 5's multiplied together
5*5*5*5*5*5
25*5*5*5*5
125*5*5*5
125*125
Answer:
TRUE
Step-by-step explanation:
Lateral area of cone is given by: πrl
where r is the radius and l is the slant height
Here r=r and l=2h
Hence, lateral area of cone A= π×r×2h
= 2πrh
Lateral area of cylinder is given by: 2πrh
where r is the radius and h is the height
Lateral area of cylinder B=2πrh
Clearly, both the lateral areas are equal
Hence, the statement that:The lateral surface area of cone A is equal to the lateral surface area of cylinder B. is:
True
Answer:
B
Step-by-step explanation:
i just need points